Pathophysiology of Atopic Dermatitis and Psoriasis: Implications for Management in Children - Raj Chovatiya; Jonathan I. Silverberg (MDPI AG, 2019)
Atopic dermatitis (AD) and psoriasis are chronic inflammatory skin diseases associated with a significant cutaneous and systemic burden of disease as well as a poor health-related quality of life. Here, we review the complex pathophysiology of both AD and psoriasis and discuss the implications for treatment with current state-of-the-art and emerging topical and systemic therapies. Both AD and psoriasis are caused by a complex combination of immune dysregulation, skin-barrier disruption, genetic factors, and environmental influences. Previous treatments for both diseases were limited to anti-inflammatory agents that broadly suppress inflammation. Emerging insights into relevant pathways, including recognition of the role of T-helper type 2 driven inflammation in AD and T-helper 1 and 17 driven inflammation in psoriasis, have led to a therapeutic revolution. There are a number of novel treatment options available for AD and psoriasis with many more currently under investigation.